Impact on Riam Kanan Irrigation to Technical Efficiency in Rice Farming System - Mustaniroh, Siti Asmaul (Jurnal Teknologi Pertanian, 2003)
This was research conducted in four villages (irrigated and non-irrigated) was designed to identify the impact of Riam Kanan Irrigation to efficiency  in rice farming system. For each villages, sample was selected by random sampling of farmers. To analyze of efficiency, use regression model according to Cobb Douglas. Next, to get frontier production use Tobit model from software SHAZAM. Results of the research  showed that on the function of production findness value of Technical Efficiency Rating (TER) first plant session (0.9958) higher than second plant session (0.9829). It means that for usefullness  of production factors in irrigated still higher than non-irrigated. Following should be implemented,  that for growing up rice production in farmer , it must be controll about irrigate and drainage system.   Keywords : impact, efficiency, rice farming system